2016
DOI: 10.1099/mic.0.000335
|View full text |Cite
|
Sign up to set email alerts
|

Novel antimicrobial peptide prevents C. rodentium infection in C57BL/6 mice by enhancing acid-induced pathogen killing

Abstract: Citrobacter rodentium is a Gram-negative, murine-specific enteric pathogen that infects epithelial cells in the colon. It is closely related to the clinically relevant human pathogen, enterohemorrhagic Escherichia coli (EHEC), a leading cause of haemorrhagic colitis and haemolytic uremic syndrome. We have previously reported that a novel antimicrobial peptide, wrwycr, compromises bacterial DNA repair and significantly reduces the survival of acid-stressed EHEC, suggesting an antimicrobial strategy for targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The combination peptide-acid treatment, which we previously demonstrated to be effective at ameliorating infection in a C. rodentium mouse model of EHEC infection (10), combines both of these effects and therefore requires two mechanisms of DNA protection though Dps, namely DNA binding and ferroxidase activity (17). This is supported by the enhanced level of bacterial killing seen in the wild-type strain when exposed to peptide-acid treatment, which is exaggerated in the dps mutant, compared to that seen with either acid or peptide treatment alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination peptide-acid treatment, which we previously demonstrated to be effective at ameliorating infection in a C. rodentium mouse model of EHEC infection (10), combines both of these effects and therefore requires two mechanisms of DNA protection though Dps, namely DNA binding and ferroxidase activity (17). This is supported by the enhanced level of bacterial killing seen in the wild-type strain when exposed to peptide-acid treatment, which is exaggerated in the dps mutant, compared to that seen with either acid or peptide treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory previously demonstrated that the D-amino acid hexapeptide WRWYCR enhances acid-induced killing of EHEC and ablates infection in a Citrobacter rodentium mouse model of EHEC infection (9,10). WRWYCR has previously been shown to bind to Holliday junctions during bacterial DNA repair and to prevent their resolution, thereby causing bacterial cell death (11,12).…”
mentioning
confidence: 99%